Translating Systems Medicine Into Clinical Practice: Examples From Pulmonary Medicine With Genetic Disorders, Infections, Inflammations, Cancer Genesis, and Treatment Implication of Molecular Alterations in Non-small-cell Lung Cancers and Personalized Medicine - Pinsolle, Julian; McLeer-Florin, Anne; Giaj Levra, Matteo; de Fraipont, Florence; Emprou, Camille; Gobbini, Elisa; Toffart, Anne-Claire (Frontiers in Medicine, 2019)
Non-small-cell lung cancers (NSCLC) represent 85% of all lung cancers, with adenocarcinoma as the most common subtype. Since the 2000’s, the discovery of molecular alterations including epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements together with the development of specific tyrosine kinase inhibitors (TKIs) has facilitated the development of personalized medicine in the management of this disease. This review focuses on the biology of molecular alterations in NSCLC as well as the diagnostic tools and therapeutic alternatives available for each targetable alteration. Rapid and sensitive methods are essential to detect gene alterations, using tumor tissue biopsies or liquid biopsies. Massive parallel sequencing or Next Generation Sequencing (NGS) allows to simultaneously analyze numerous genes from relatively low amounts of DNA. The detection of oncogenic fusions can be conducted using fluorescence in situ hybridization, reverse-transcription polymerase chain reaction, immunohistochemistry, or NGS. EGFR mutations, ALK and ROS1 rearrangements, MET (MET proto-oncogenereceptor tyrosine kinase), BRAF (B-Raf proto-oncogen serine/threonine kinase), NTRK (neurotrophic tropomyosin receptor kinase) and RET (ret proto-oncogene) alterations are described with their respective TKIs, either already authorized or still in development. We have herein paid particular attention to the mechanisms of resistance to EGFR and ALK-TKI. As a wealth of diagnostic tools and personalized treatments are currently under development, a close collaboration between molecular biologists, pathologists, and oncologists is crucial.